Job Satisfaction as a Mediator of Compensation and Motivation on Employees Performance - Diandra Fachiroh; Andriyastuti Suratman (Universitas Medan Area, 2023)
This study is intended to understand how job satisfaction acts as a mediator in influencing the rela-tionship between compensation and motivation to employee performance. Pertamina Hospital Cirebon was chosen as the object of the study. A quantitative approach was used in this study, with data collection through questionnaires using Google Form. The population amounted to 199 and the sample used was 150 people. The sampling method used was purposive random sampling, with the criteria that employees have the status of specific time workers (PWT) and non-specific time workers (PWTT). Data analysis is validity and reliability test, classical assumption test, descriptive statistical analysis, simple and multiple linear regression analysis, and sobel test using SPSS software version 25. The results showed that both compensation and motivation have a positive and significant effect on employee performance and job satisfaction. Job satisfaction has a positive and significant effect on employee performance. In addition, this study indicates that job satisfaction can mediate the relationship between compensation and moti-vation to employee performance.